Key neuroprotective mechanisms of the MIND diet - a review paper - Weronika Szafrańska; Weronika Kahan; Dominika Poborowska; Marta Wojaczek; Katarzyna Polańska; Magdalena Kras; Agnieszka Kosińska; Piotr Niedbał; Katarzyna Lelek; Marcin Łata (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Impaired cognitive function is a growing public health problem, where dementia is affecting about 47 million people worldwide, and that number is expected to triple by 2050. The MIND (Mediterranean-DASH Intervention for Neurodegenerative Delay) diet is intended to overcome this problem. This article aims to raise awareness of the MIND diet, highlighting how dietary choices can promote cognitive health and delay disease progression. Brief description of the state of knowledge: The MIND diet focuses on foods that support cognitive health and may mitigate these degenerative processes. It emphasizes green leafy vegetables, berries, nuts, olive oil, whole grains, fish, and poultry while limiting red meat, dairy, sweets, and fried foods. These products contain several components with multidirectional neuroprotective effects. Material and method: This work was based on material found on Google Scholar. Articles were selected based on citation counts, publication dates, and relevance, ensuring a comprehensive review of recent findings on the MIND diet's impact on cognitive health. Summary: The MIND diet enhances brain health by incorporating nutrient-dense foods that reduce inflammation, combat oxidative stress, and support neuronal function. Green leafy vegetables, berries, nuts, whole grains, and healthy fats work together to improve cognitive function, support synaptic plasticity, and protect brain structure, leading to slower cognitive decline and a lower risk of neurodegenerative diseases.